Customer satisfaction index with the implementation of a handbook in English as a foreign language in hotel de la ópera restaurants (2016)
Hotel de la Opera was born from the restoration and joining of two distinguished and renowned houses next to El Teatro Colón, built during the 19th and 20th centuries. The hotel offers a warm, quiet and unique atmosphere, with generous areas and balconies that look over the cobblestone streets, an unforgettable memory of your stay in the capital city of Colombia. This has two places to eat, La Scala and El Mirador which offer a select combination of Mediterranean, International and local dishes in the Bogotá tradition. In this case, the investigation focuses on the customers and staff members from the Hotel restaurants.